Differential Expression of IL-6 and IGF-II in Guinea Fowl and Chicken - Goyal, G.; Upmanyu, V.; Singh, S.K.; Shukla, S.K.K.; Mehra, S.; Kumar, Vinay; Sharma, Deepak (International Journal of Poultry Science, 2010)
Differential expression of IL-6 and IGF-II genes were studied in guinea fowl and broiler chicken using semi-quantitative analysis. A 219 bp fragment of IL-6 and 215 bp fragment of IGF-II were amplified in guinea fowl and broiler chicken using chicken specific primers. Semi-quantitative analysis revealed the adjusted Integral Density of 0.853 and 0.051 for IL-6 band in guinea fowl and broiler chicken respectively, revealing 16.62 fold higher IL-6 mRNA expression in LPS induced PBMCs from guinea fowl as compared to that from broiler. However, adjusted Integral Density of IGF-II band was 0.082 and 1.106 for IGF-II band in guinea fowl and broiler chicken respectively, which revealed 13.43 fold increase in IGF-II mRNA expression in LPS induced PBMCs in broiler chicken as compared to that in guinea fowl. Hence, guinea fowl showed higher expression of pro-inflammatory cytokine (IL-6) and lower expression of IGF-II in comparison to broiler chicken. These findings were as per expectation in view of much higher immuno-competence and lower growth rate in guinea fowl in comparison to chicken.